Indian millets trade potential-cum-performance: Economic perspective - SINGH, PARDEEP; ARORA, KASHISH; KUMAR, SUNNY; GOHAIN, NAMAMI; SHARMA, RAMANDEEP KUMAR (The Indian Journal of Agricultural Sciences, 2023)
The present study examines the trade performance of millets, competitiveness and their impact on the country’s growth in the agriculture sector. Empirical findings revealed that Indian millet exports contributed significantly to the global basket from the year 2000–2020 and had a huge potential in the international market. During the year 2011–2020, India’s major exporting partners were neighbouring countries, i.e. Pakistan, Vietnam, Nepal and Saudi Arabia, wherein India exported more than 50% of the country’s millet export. The study looked at India’s comparative advantage of millets by country by using Revealed Comparative Advantage (RCA), and the results showed that Pakistan, Saudi Arabia, Vietnam, and Yemen were the major millet importing countries exhibiting RCA value greater than one, indicating that India had a significant advantage in exporting millets to these partner countries during the recent study period (2011–2020). Furthermore, gravity model is calibrated by using the variables like Gross Domestic Product (GDP), exchange rate and population of the respective countries. The results of the gravity model suggested that the country's GDP would grow with an increase in millets exports in India, but the country's exports would decrease with an increase in population.